IMPLEMENTASI SISTEM KONTROL PLC PADA TRAINER PENGOLAHAN AIR LIMBAH DI SMK NEGERI 5 BITUNG - Stivmark Lumentut, Jhosua; Rolly Kambey, Valentino; Vannes Rey, Mirachle; Kasenda, Sonny; Pongoh, Johan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Wastewater treatment is one of the important processes in maintaining environmental sustainability and public health. In vocational education, especially in Vocational High Schools, learning media are needed that are able to provide a practical and applicable understanding of the wastewater treatment process integrated with industrial automation technology. One of the technologies widely used in control systems commonly applied in industry is the Programmable Logic Controller (PLC). Therefore, this research focuses on the design and implementation of an Omron PLC-based control system in a wastewater treatment trainer as a learning medium at SMK Negeri 5 Bitung. The methods used include the control system design stage, the preparation of control logic, programming the Omron PLC using ladder diagrams, and planning system function testing on the wastewater treatment trainer. The control system is designed to process input signals from sensors and produce output signals that control actuators, such as pumps and indicators, according to the predetermined sequence of wastewater treatment processes, with reference to the working principles of control systems commonly used in industry to make it suitable for use as a learning medium. The Omron PLC-based wastewater treatment trainer that was designed is expected to be used as a practical learning tool that supports vocational school students' understanding of the working principles of PLC-based control systems, wastewater treatment process flows, and the relationship between sensors, controllers, and actuators in a structured manner, so that industrial automation learning in vocational schools can take place more effectively and applicably